Biomechanical factors that influence intra-individual variations in step frequency and length during sprinting - Toyoshima, R.; Tauchi, K.; Endo, T.; Iso, S.; Sakurai, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2015)
The purpose of this study was to clarify the biomechanical factors that influence intra-individual variations in step frequency (SF) and length (SL) during sprint running. One male sprinter participated as a study subject, and performed a 60-m sprint at maximal effort. Experiments were conducted 5 times, with a total number of 14 trials. The ground reaction force and positions of markers attached to the joints were recorded using force plates and a motion capture system. Trials were divided into SF type and SL type depending on the SF/SL ratio, and the kinematic variables and ground reaction force were compared. The main results were as follows. 1) There were no significant differences in sprint velocity and stance time between the SF type and the SL type. 2) The flight time of the SL type was longer than that of the SF type. 3) Vertical components of the ground reaction force and impulse during the stance phase were larger for the SL type than for the SF type. 4) The thigh angle of the swing leg was larger for the SL type than for the SF type during almost all phases. 5) The hip joint of the swing leg was flexed to a greater degree during the stance phase and first half of the flight phase for the SL type than for the SF type. 6) There were no marked differences in the segment and joint angular velocities between the SF type and the SL type. These results indicate that changes in step frequency and step length with flight time are due to an increase or decrease of vertical impulse. Moreover, it was revealed that vertical impulse is influenced by the thigh angle of the swing leg during the stance phase, rather than by the angular velocity of the swing leg.